Deliberate practice in motivational interviewing - Manuel, Jennifer K.; Ernst, Denise B.; Vaz, Alexandre; Rousmaniere, Tony (Essentials of deliberate practice, 2022)
"Deliberate practice exercises facilitate the rehearsal of fundamental motivational interviewing skills so clinicians can better help clients with change goals, like quitting addictive behaviors and developing healthier habits"--Provided by publisher.